Studying Verb Types in the Lessons of Russian as a Foreign Language - Alaudinova Rukhsora (Zien Journals, 2022)
The article considers the methodology for teaching foreign listeners the use of perfective and imperfective verbs at the elementary level of mastering the Russian language. Ways of forming specific pairs of verbs are presented, language exercises are given to consolidate this material.
Keywords: perfect; imperfect; verb; tense